New Field Effect Deep‐UV μLEDs Development. Issue 10 (15th May 2018) - Rottner, Jean; Haas, Helge; Largeron, Christophe; Vaufrey, David; Robin, Ivan. C.
Abstract : Mg‐doped AlGaN layers are needed for deep‐ultraviolet light emitting diodes (DUV‐LEDs). However because of the high activation energy of Mg in such layers, the ionization level of the Mg‐dopants is very low. In this paper a new design is proposed with a view to improve the wall plug efficiency (WPE) of DUV‐LEDs. The method consists in using a geometry combining a UV‐ μ LED and a gate covering the edges of the mesa. This approach is intended to by‐pass the problem of low ionization level of the dopants in p‐AlGaN. The simulated structures include a DUV‐LED mesa structure with Al0.5 Ga0.5 N/Al0.7 Ga0.3 N multiple quantum well (MQW) active region emitting around 265 nm. It also comprises a gate deposited on the sidewalls of the mesa. Simulations performed with Silvaco atlas will be presented. In particular we will show that by applying an appropriate voltage to the gate, holes can be efficiently injected into the active region. They reach the active region via an accumulation channel below the gate around the mesa, and then diffuse along the length of wells and easily recombine with electrons. Finally simulations show that the calculated WPE can be increased by a factor of 3 for an optimized structure geometry. Abstract : This paper presents a new concept of deep‐UV LED to overcome the doping issue of p‐AlGaN. By adding a gate on the sidewall of the p‐layer and the active area, the simulated wall plug efficiency of the structure is increased by a factor of 3 at a 3V lower working voltage.